2019
DOI: 10.1002/ece3.5311
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of “supermoon” events on the physiology of a wild bird

Abstract: The position of the Moon in relation to the Earth and the Sun gives rise to several predictable cycles, and natural changes in nighttime light intensity are known to cause alterations to physiological processes and behaviors in many animals. The limited research undertaken to date on the physiological responses of animals to the lunar illumination has exclusively focused on the synodic lunar cycle (full moon to full moon, or moon phase) but the moon's orbit—its distance from the Earth—may also be relevant. Eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 68 publications
(85 reference statements)
2
11
1
Order By: Relevance
“…Indeed, the daily amount of NREM sleep was 2.0 h lower during full moon than during new moon. This finding appears to be in agreement with earlier reports showing that barnacle geese are more active and have an increased heart rate and body temperature during nights with a full moon [ 52 ]. Also, our own recent work in starlings showed that this songbird on average sleeps 2 h less on nights with a full moon [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the daily amount of NREM sleep was 2.0 h lower during full moon than during new moon. This finding appears to be in agreement with earlier reports showing that barnacle geese are more active and have an increased heart rate and body temperature during nights with a full moon [ 52 ]. Also, our own recent work in starlings showed that this songbird on average sleeps 2 h less on nights with a full moon [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…The full moon on 8 April 2020, which is an example of a recent supermoon, was 14% larger in apparent diameter than the smallest full moon, or “micro–full moon,” on 31 October 2020 (NAOJ, 2020). Scientists suggest that the supermoon can also affect some natural phenomena (e.g., Portugal et al, 2019). It has greater gravitational force than the normal full or new moon and produces a larger tidal range, in particular the high tide known as the “king tide” (Flick, 2016; NOAA, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the completion of moult, the 95 newly grown 9 th primary feather was removed. Flight feathers from wild Barnacle Geese were collected during wing moult, at Ny-Ålesund, Spitsbergen (78°55′N 11°56′E78.917°N 11.933°E,)(see Portugal et al 2011c;Portugal et al, 2019a;Portugal et al,. 2019b).…”
Section: Feather Samples 90mentioning
confidence: 99%